Earl Rögnvaldr of Orkney, a poet of the Viking diaspora - Jesch, Judith (Eagle Hill Institute, 2013)
Kali Kolsson, later Rögnvaldr, Earl of Orkney, is a truly international figure who was born in Norway, travelled to England, came to power in Northern Scotland, and then made a memorable journey through Europe and the Mediterranean to the Holy Land. His poetry, composed in all of these places, survives only in Icelandic tradition and Icelandic manuscripts. This paper argues that the career and poetry of Rögnvaldr exemplifies the variation typical within a dispersed but interconnected culture, which might be termed the “Viking diaspora”. Rögnvaldr was by training a Norwegian poet, but by practice and influence an Icelandic and Orcadian—indeed a European—poet. Each of these places had its own version of the culture, some of which shared a common derivation from the Scandinavian homeland, but much of which was rather the product of the dispersion from that homeland. By examining his poetry, and his interest in runic writing, it is possible to exemplify the diasporic process in which inherited cultural traditions from the homeland are reinvigorated and even reinvented in the context of multilateral cultural encounters.